Mechanically robust sodium alginate/cellulose nanofibers/polyethyleneimine composite aerogel for effective removal of hexavalent chromium and anionic dyes - Xie, Qian; Zou, Yuke; Wang, Yazhou; Wang, Haibo; Du, Zongliang; Cheng, Xu (Polymer engineering and science, 2022)
To improve the mechanical properties and adsorption capacity of sodium alginate aerogel (SA), cellulose nanofibers were used as reinforcing fillers, and polyethyleneimine (PEI) was used as a crosslinker to reinforce the SA aerogel. Moreover, PEI provided functional groups to adsorb Cr(VI) and anionic dyes (Congo red [CR] and Methyl orange [MO]) through electrostatic and coordination action. The biomass aerogel adsorption materials were characterized by Fourier transform infrared spectroscopy, scanning electron microscope, energy dispersive spectroscopy, x‐ray photoelectron spectroscopy, and so on. The results showed that the maximum adsorption capacity of the composite aerogel adsorbent for Cr(VI), CR, and MO under the optimal pH value was 726.59, 2007.48, and 2253.38 mg/g, respectively. Langmuir model and quasi‐second‐order kinetics can be employed to reasonably describe the adsorption process of Cr(VI) and anionic dyes. Compared with other reported adsorption materials, this biomass composite aerogel has notable advantages such as simple preparation, economical application, high adsorption capacity, convenient recycling, and environmental. Preparation and adsorption properties of SCP.